Ansible Quick Start Guide : Control and Monitor Infrastructures of Any Size, Physical or Virtual. - Alibi, Mohamed (Packt Publishing Ltd, 2018)
Configuration Management (CM) tools help administrators reduce their workload. Ansible is one of the best Configuration Management tools, and can act as an orchestrator for managing other CMs. This book is the easiest way to learn how to use Ansible as an orchestrator and a Configuration Management tool. With this book, you'll learn how to ...